Rubber curing chemistry governing the orientation of layered silicate (eXPRESS Polymer Letters, 2007)
The effect of curing systems on the orientation and the dispersion of the layered silicates in acrylonitrile butadiene rubber nanocomposite is reported. Significant differences in X-ray diffraction pattern between peroxide curing and sulfur curing was observed. Intense X-ray scattering values in the XRD experiments from peroxide cured vulcanizates indicate an orientation of the layers in a preferred direction as evinced by transmission electron micrographs. However, sulfur cured vulcanizates show no preferential orientation of the silicate particles. Nevertheless, a closer inspection of transmission electron microscopy (TEM) images of peroxide and sulfur cured samples shows exfoliated silicate layers in the acrylonitrile butadiene rubber (NBR) matrix. It was revealed in the prevailing study that the use of an excess amount of stearic acid in the formulation of the sulfur curing package leads to almost exfoliated type X-ray scattering pattern.